Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1-Mediated Autophagy in Human Granulosa Cells as an Alternative of Programmed Cell Death - Nicole Duerrschmidt; Olga Zabirnyk; Marcin Nowicki; Albert Ricken; Fayez A. Hmeidan; Verona Blumenauer; Jürgen Borlak; Katharina Spanel‐Borowski (2006)
The LOX-1 receptor, identified on endothelial cells, mediates the uptake of oxidized low-density lipoprotein (oxLDL). The oxLDL-dependent LOX-1 activation causes endothelial cell apoptosis. We here investigated the presence of LOX-1 in granulosa cells from patients under in vitro fertilization therapy. We were interested in the oxLDL-dependent LOX-1 receptor biology, in particular in the induction of apoptosis. In the human ovary, LOX-1 was localized in regressing antral follicles. In granulosa cell cultures, oxLDL-induced mRNA expression of LOX-1 in a time- and dose-dependent manner. The LOX-1 inhibitors (anti-LOX-1 antibody and kappa-carrageenan) abrogated the up-regulation of LOX-1. The oxLDL (100 microg/ml) treatment caused the autophagy form of programmed cell death: 1) reorganization of the actin cytoskeleton at the 6-h time point; 2) uptake of YO-PRO, a marker for the early step of programmed cell death, before propidium iodide staining to signify necrosis; 3) absence of apoptotic bodies and cleaved caspase-3; 4) abundant vacuole formation at the ultrastructural level; and 5) decrease of the autophagosome marker protein MAP LC3-I at the 6-h time point indicative of autophagosome formation. We conclude that follicular atresia is not under the exclusive control of apoptosis. The LOX-1-dependent autophagy represents an alternate form of programmed cell death. Obese women with high blood levels of oxLDL may display an increased rate of autophagic granulosa cell death.